2006
DOI: 10.1103/physrevd.73.083004
|View full text |Cite
|
Sign up to set email alerts
|

Analytical formulas for gravitational lensing

Abstract: In this paper we discuss a new method which can be used to obtain arbitrarily accurate analytical expressions for the deflection angle of light propagating in a given metric. Our method works by mapping the integral into a rapidly convergent series and provides extremely accurate approximations already to first order. We have derived a general first order formula for a generic spherically symmetric static metric tensor and we have tested it in four different cases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
80
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(85 citation statements)
references
References 32 publications
5
80
0
Order By: Relevance
“…As pointed out in [26] in the Schwarzschild case, the 1/b expansion for the deflection angle does not reproduce the photon sphere singularity of the Schwarzschild metric, which is achieved using the exact GR expression in terms of elliptic function given in (8.14), but it represents nevertheless an improvement respect to the 0P N order. Expanding the RN metric in M/ρ 1 up to the third order, the 2P N approximation gives…”
Section: Post Newtonian Contributions In Classical Grmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out in [26] in the Schwarzschild case, the 1/b expansion for the deflection angle does not reproduce the photon sphere singularity of the Schwarzschild metric, which is achieved using the exact GR expression in terms of elliptic function given in (8.14), but it represents nevertheless an improvement respect to the 0P N order. Expanding the RN metric in M/ρ 1 up to the third order, the 2P N approximation gives…”
Section: Post Newtonian Contributions In Classical Grmentioning
confidence: 99%
“…This has been studied quite carefully in the literature, especially in the limit of strong lensing [26,27]. The 1/b n h expansion has been shown to appear quite naturally in the post-Newtonian approach applied to the Einstein integral for light deflection.…”
Section: /B N Contributions To the Deflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method provides several advantages over other well established methods in the literature: first of all, to the best of our knowledge our method is the only nonperturbative method which allows to obtain fully analytical results and for which the exponential convergence of the series is proved ( [6,7,8]); secondly, previous work done in [6,7,8], where the method was used to calculate the period (and not the solution) has shown that our method can be used for a quite large of class of potentials, even in cases where the exact result cannot be obtained; finally it is easy to calculate higher order contributions (never involving special functions) with our method.…”
Section: Discussionmentioning
confidence: 99%
“…While other techniques are been developed in the literature to deal with this problem, see for example [1,2], we wish to present a novel method which was recently devised by one of us [6,7,8] and which allows one to calculate accurate analytical solutions for a classical oscillator, described by Eq. (1).…”
Section: Introductionmentioning
confidence: 99%